Assessing the Relationship in Symptomology of Myalgic Encephalitis/Chronic Fatigue Syndrome and Long COVID - Garapaty, Nikitha; Reyes, Kristina M.; Tehrani, Lily; Mendoza, Maximiliano Barbosa; Hardigan, Patrick (American journal of medicine open, 2025)
•Long COVID alone is less likely to express symptomology than ME/CFS alone.•ME/CFS and long COVID are more likely to express symptomology than conditions alone.•A greater number of women are reported to have these conditions. The symptomology of Myalgic Encephalitis/Chronic Fatigue Syndrome (ME/CFS) shares many commonalities with Long COVID (LC). This study aimed to clearly define the comparison between ME/CFS and LC in terms of symptomology. A cross-sectional analysis of 27,651 interviewees from a National Health Interview Survey 2022 adult dataset was conducted. The data was controlled for subject's sex, race/ethnicity, age, life satisfaction, insurance coverage, poverty ratio, and comorbidities. A logistic regression was used to compare four groups: (1) LC individuals, (2) ME/CFS individuals, (3) LC with ME/CFS individuals, and (4) controls by symptoms of depression, anxiety, physical activity, fatigue, and memory. The results showed that subjects with both ME/CFS and LC were more likely to report memory issues, anxiety, depression, fatigue, and difficulty with physical activity followed by subjects with ME/CFS only, LC only, and the controls (P < .01). Our study suggests a synergistic mechanism between ME/CFS and LC in developing issues with anxiety, depression, fatigue, and physically activity in patients. The study's conclusions highlight the need to elucidate the possible overlap in pathophysiological mechanisms of ME/CFS and LC in the symptomology of patients.